The use of the Decision Regret Scale in non-clinical contexts - Diotaiuti, Pierluigi; Valente, Giuseppe; Mancone, Stefania; Grambone, Angela; Chirico, Andrea; Lucidi, Fabio (Frontiers in Psychology, 2022)
The study evaluated the psychometric properties of the Decision Regret Scale (DRS) to measure decision regret related to choice scenarios in everyday life. Although previous studies have usually employed the scale with patients and in the context of medical decision-making, this contribution shows that the instrument may have a variety of uses, retaining excellent metric properties even in non-medical contexts. The tool showed good fits with both the CFA (χ2 = 6.019; df = 4; CFI = .999; TLI = .996; RMSEA = .024) and the gender Measurement Invariance. A total of 2,534 Italian university students participated in a non-probabilistic sampling. The internal consistency measures were found to be fully satisfactory. Convergent validity was tested by the correlations with the General Decision-Making Style (GDMS) and Scale of Regulatory Modes (SRM). Convergence analysis showed that participants with higher regret scores were those who favoured a rational decision-making style, while lower regret scores correlated with avoidant and spontaneous styles. With regard to the regulatory modes, the relationship between regret and locomotion was positive. Overall, the directions of association point to an interesting predictive measure of a person’s decision-making and self-regulatory orientation through the evaluation of regret using the DRS. The excellent psychometric properties found foreshadow a reliable use in various contexts where knowledge of post-decisional attitude becomes important: school, university, professional orientation, marketing studies, relationship choices, as well as for use in research.